2020
DOI: 10.25133/jpssv28n2.008
|View full text |Cite
|
Sign up to set email alerts
|

Mental Well-being, and Coping Strategies during Stress for Preclinical Medical Students in Vietnam

Abstract: Inappropriate coping strategies may be key factors that have contributed to a consistently high prevalence of stress and mental disorders that have been reported worldwide, particularly in resourcelimited countries. Thus, one aim of this paper is to estimate the prevalence of these inconstructive strategies, and explore more positive coping strategies through observation of undergraduate medical students in Vietnam. The methodology that has been employed for this project has been a cross-sectional analysis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
2
6
1
2
Order By: Relevance
“…The students also highlighted the importance of mental health support that may affect their performance and satisfaction. Similarly, studies have highlighted that stress reduction and management are effective for the health and well-being of students who will eventually become the future doctors taking care of physical and mental wellbeing of other (Huynh et al, 2020;Kötter et al, 2019). Conley, Kirsch, Dickson and Bryant (2014) reported that students' involvement in extracurricular activities can improve their mental health which is confirmed by our students' opinion who believed that involvement in extracurricular activities may shape their personality and develop transferable skills.…”
Section: Discussionsupporting
confidence: 66%
“…The students also highlighted the importance of mental health support that may affect their performance and satisfaction. Similarly, studies have highlighted that stress reduction and management are effective for the health and well-being of students who will eventually become the future doctors taking care of physical and mental wellbeing of other (Huynh et al, 2020;Kötter et al, 2019). Conley, Kirsch, Dickson and Bryant (2014) reported that students' involvement in extracurricular activities can improve their mental health which is confirmed by our students' opinion who believed that involvement in extracurricular activities may shape their personality and develop transferable skills.…”
Section: Discussionsupporting
confidence: 66%
“…The students also highlighted the importance of mental health support that may affect their performance and satisfaction. Similarly, studies have highlighted that stress reduction and management are effective for the health and well-being of students who will eventually become the future doctors taking care of physical and mental wellbeing of other (Huynh et al, 2020;Kötter et al, 2019). Conley et al (2014) reported that students' involvement in extracurricular activities can improve their mental health which is confirmed by our students' opinion who believed that involvement in extracurricular activities may shape their personality and develop transferable skills.…”
Section: Discussionsupporting
confidence: 66%
“…An integrated model consisting of dedicated counseling sessions for medical students, wellness group activities, online courses, and collaboration with student health services for referral (e.g., psychiatric counseling) is employed at Florida International University to reduce burnout and depression as byproducts of studying medicine [ 14 ]. One study calls for developing stress management programs through training workshops to prevent mental health conditions in medical schools given the high prevalence of such disturbances among medical students [ 15 ]. Considering the extra psychological burden that the current pandemic has put on medical students, student support systems’ employment seems more essential than ever before [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%